Recovery and amplification of touch DNA on porous surfaces using modified chelex extraction method - Mun, Nayomi Khoo Ya (Universiti Sains Malaysia, 2025)
Prayer is an obligation of every individual Muslim in any condition and situation. The obligation to perform prayer is not dropped even in a state of illness or difficult situation. Learning about prayer when sick is seen to enter a new dimension when the rapid development of information technology is fully utilized. However, the difference in views among sects regarding the approach to prayer when sick means that some patients are treated in hospitals that do not perform prayer. The lack of knowledge about prayer procedures when ill and the relief provided by Islam also leads to a lack of prayer practice. This study aims to verify the questionnaire through the validation and reliability process, develop the Patient Prayer Digital Health Education website (PKDSP), and intervene on the website. A total of 174 respondents were involved in the pre-and post-study phases using the 'snowball' sampling method. The results of the questionnaire validity study show that the construct of knowledge and practice is a validated instrument when it meets the suitability requirements of the questionnaire model by producing the construct of knowledge: PCMIN/DF: 1.46, GFI: 0.96, CFI: 0.95 and RMSEA 0.05 and the construct of practice: PCMIN/DF: 2.04, GFI: 0.93, CFI: 0.90 and RMSEA 0.75. The Cronbach's alpha values obtained for the knowledge and practice sections are 0.66 and 0.64, respectively, which are accepted values for the reliability of a questionnaire. The results of the pre- and post-tests showed that there was an increase in the respondents' knowledge pre-test which was 9.94 and post-test which was 12.24 with a standard deviation (SD) of 1.95 after referring to the PKDSP website. Meanwhile, the average value (mean) also showed an increase in the respondents' practice pre-test which was 7.06 and post-test which was 17.76 with a standard deviation (SD) of 3.25. This study also used the Mobile Application Usability Scale (SKAMA) to evaluate the Patient Prayer Digital Health Education website (PKDSP) used in the post-study phase. The findings show that respondents who used the PKDSP website for the post-phase obtained an average value of 77.28 (SD 16.78), passing the cutoff value 68 for application usability score based on SKAMA the proposed Mobile Application Usability Scale (SKAMA) score. In conclusion, the PKDSP website that was developed has had the impact of increasing knowledge and practice for the respondents involved. Therefore, this PKDSP website is expected to help Muslims improve their knowledge and practice when they are ill, whether they receive treatment in a hospital or not.